Achieving progress through clinical governance? A national study of health care managers' perceptions in the NHS in England. Issue 5 (1st October 2004) - Freeman, T; Walshe, K
Abstract : Background: A national cross sectional study was undertaken to explore the perceptions concerning the importance of, and progress in, aspects of clinical governance among board level and directorate managers in English acute, ambulance, and mental health/learning disabilities (MH/LD) trusts. Participants: A stratified sample of acute, ambulance, and mental health/learning disabilities trusts in England (n = 100), from each of which up to 10 board level and 10 directorate level managers were randomly sampled. Methods: Fieldwork was undertaken between April and July 2002 using the Organisational Progress in Clinical Governance (OPCG) schedule to explore managers' perceptions of the importance of, and organisational achievement in, 54 clinical governance competency items in five aggregated domains: improving quality; managing risks; improving staff performance; corporate accountability; and leadership and collaboration. The difference between ratings of importance and achievement was termed a shortfall. Results: Of 1916 individuals surveyed, 1177 (61.4%) responded. The competency items considered most important and recording highest perceived achievement related to corporate accountability structures and clinical risks. The highest shortfalls between perceived importance and perceived achievement were reported in joint working across local health communities, feedback of performance data, and user involvement. When aggregated into domains, greatest achievement was perceived in the assurance related areas of corporate accountability and risk management, with considerably less perceived achievement and consequently higher shortfalls in quality improvement and leadership and collaboration. Directorate level managers' perceptions of achievement were found to be significantly lower than those of their board level colleagues on all domains other than improving performance. No differences were found in perceptions of achievement between different types of trusts, or between trusts at different stages in the Commission for Health Improvement (CHI) review cycle. Conclusions: While structures and systems for clinical governance seem well established, there is more perceived progress in areas concerned with quality assurance than quality improvement. This study raises some uncomfortable questions about the impact of CHI review visits.